Pidgin and Creole Linguistics - Valdman, Albert (Indiana University Press, 1977)
This volume of essays constitutes an up-to-date survey of pidgin and creole linguistics intended for general linguists and readers interested in current theory in such diverse areas as linguistic universals, language acquisition, bilingualism, and language planning. It will acquaint persons relatively unfamiliar with the field with established theories and data, enabling them to follow current debates and to undertake research in the field. Thus it may serve as a basic textbook in courses in sociolinguistics, bilingualism, and language contact, as well as in ethno- or anthropological linguistics, whose focus is language variation and its social and cultural implications. The volume includes a global survey of the distribution of pidgin and creole languages, accompanied by a world distribution map and detailed maps of the Caribbean and other areas. Contributors to this work are Albert Valdman, David DeCamp, Pieter Muysken, Guus Meijer, Derek Bickerton, Elizabeth Closs Traugott, Charles A. Ferguson, Charles E. DeBose, Gabriel Manessy, John R. Rickford, Robert Le Page, Robert Chaudenson, Ian F. Hancock, Keith Whinnom, Dennis R. Craig, and Stephen A. Wurm.